Islamic Jurisprudence Study on Organ Transplantation (Transplantation) - Pairuz Amanina; Yardah Annisi Ahdy Sitorus; Riyan Saputra Sinaga (Jurnal Sahabat ISNU SU, 2025)
This paper examines the practice of organ transplantation from the perspective of contemporary Islamic jurisprudence. The background of the research is based on advances in medical technology that enable organ transplantation as a solution to organ failure, but also raises ethical and legal issues in Islam. This study uses a library research method by reviewing fatwas, opinions of scholars, and contemporary Islamic jurisprudence references. The research stages begin with collecting literature data, analyzing the opinions of classical and contemporary scholars, and compiling legal conclusions. The results of the study indicate that the majority of scholars permit organ transplantation in emergencies under certain conditions such as not endangering the donor, being carried out voluntarily, and not for commercial purposes. Transplants from corpses and non-Muslims are also permitted if they fulfill the principles of maqāṣid al-syarī'ah, especially hifẓ al-nafs (protecting the soul). Meanwhile, transplants from halal animals are permitted, while those from unclean animals such as pigs are only permitted in emergencies. A strict prohibition is imposed on the sale and purchase of body organs, because it is contrary to the principle of respect for the human body in Islam.